Democracy and Corruption Causality in Indonesia - Azwar Iskandar; Achmat Subekan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The objective of this study is to analyze the causality between democracy and corruption in Indonesia for the period of 1995 to 2017. This study perform a multivariate cointegration test with government expenditure as a control variable and cross-check this long-run relationship with an Autoregressive Distributed Lag (ARDL) model approach to cointegration beside multivariate approach proposed by Johansen & Juselius. The results show that there is cointegration among the variables specified in the model of corruption equation when government expenditure is taken into account. Indeed, for corruption and democracy to move together in the long run, they need to be associated with government expenditure. The tests for Granger Causality conducted show a long-run causality running from democracy and government expenditure to corruption. In other word, the democracy and government expenditure Granger cause corruption and not the reverse. In short-run, there is neutrality causation between democracy and corruption.